In- and exclusion in urban food governance: Exploring networks and power in the city of Almere - Brons, Anke; Oosterveer, Peter; Wertheim-Heck, Sigrid C.O. (Informa UK Limited, 2022)
Cities are becoming involved in food governance, with a shift to multi-actor urban food governance taking place. Yet, not all food system actors are equally represented in these governance processes. Facing challenges on participation and social justice, questions arise on how inclusive urban food governance is in practice. This article aims to provide a contribution to this debate by looking at the city of Almere, the Netherlands, in the development of its first urban food strategy (UFS). By assessing the governance network involved in the creation of the UFS this article studies mechanisms of in- and exclusion within this process. Conceptually, the article builds on Manuel Castells’ network theory of power. Methodologically, the article presents a network analysis integrated with qualitative methods. The article finds that the municipality is at the network's centre, trying to balance inclusive versus efficient governance. This highlights the tensions around inclusion in network governance, as a network is only responsible for those included in the network, whereas governments are ultimately responsible for all of their citizens, even if they are not directly included in the governance network. This calls for further reflection on the roles of citizens in urban food governance in a network society.